PENGARUH LINGKUNGAN KERJA DAN KEDISIPLINAN TERHADAP KINERJA KARYAWAN DI PT TRANSCAL SUNTECH INTERNATIONAL - Shelly, Shelly; Wasiman, Wasiman (LPPM Universitas Putera Batam, 2021)
This research has objective to find out the effect of work environment and discipline against employees’ performance in PT Transcal Suntech International. The research was using quantitative method. The data was obtained based on 115 people’s answer that participated in questionnaries. The data that already collected will be analyzed by using SPSS version 25 helping tool. This research showed that the result for the coefficient of determination (R2) was giving value 0.750. It concluded that the work environment and discipline give 75,00% of effect to performance of employees at PT Transcal Suntech International and 25,00% remaining was influenced by different variable that unincluded as research variable